An unusual cause of hematospermia: Primary adenocarcinoma of the seminal vesicle - Eken, Alper; Izol, Volkan; Aridogan, I. Atilla; Erdogan, Seyda; Acikalin, Arbil; Tansug, Zuhtu (Canadian Urological Association Journal, 2012)
Adenocarcinoma of the seminal vesicles is one of the rare causes of hematospermia. Primary seminal vesicle adenocarcinoma is extremely rare and difficult to diagnose due to frequent invasion of adenocarcinomas of the surrounding organs, especially the prostate. In the present study, a case of a primary seminal vesicle adenocarcinoma will be discussed in the light of the current literature.